1999
DOI: 10.1159/000054492
|View full text |Cite
|
Sign up to set email alerts
|

An Opioid Pathway in the Hypothalamus of the Turkey That Stimulates Prolactin Secretion

Abstract: Circulating prolactin (PRL) levels increase when dynorphin is infused into the turkey brain. This study tested the hypothesis that centrally infused dynorphin requires an intact vasoactive intestinal peptide (VIP) system in order to stimulate turkey PRL secretion. It also investigated the roles of the dopaminergic and serotonergic systems in dynorphin-induced PRL release. Drugs were infused into the third ventricle of anesthetized laying turkeys via stereotaxically guided cannulae and circulating blood was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The postulated photic route may be part of a serial pathway involving 5-HT, DA and VIP [16]. 5-HT, infused centrally, has been shown to increase circulating PRL in all reproductive stages except short-day birds [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postulated photic route may be part of a serial pathway involving 5-HT, DA and VIP [16]. 5-HT, infused centrally, has been shown to increase circulating PRL in all reproductive stages except short-day birds [28].…”
Section: Discussionmentioning
confidence: 99%
“…DA plays an intermediary role in PRL secretion, requiring an intact VIPergic system in order to cause the release of PRL [2]. Serotonin (5-HT) and the opioid dynorphin also stimulate avian PRL secretion and both require an intact dopaminergic system, as well as an intact VIPergic system [13, 14, 15, 16]. Dynorphin, 5-HT, DA and VIP all appear to stimulate avian PRL secretion along a pathway expressing ĸ opioid, serotonergic, dopaminergic and VIPergic receptors at synapses arranged serially, with the VIPergic system as the final mediator [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, dopamine has been found to antagonize the ovary‐stimulating action of serotonin in P. clarkii [19]. Moreover, it is known that dopamine has a regulatory effect on prolactin secretion from vertebrate pituitary cells; a high concentration of dopamine inhibits prolactin release, whereas a low concentration of dopamine stimulates prolactin secretion [20,21]. However, we do not know at present whether such dopamine functions are related to the induction of diapause in silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…The GnRH‐I/LH, folicle‐stimualting hormone (FSH) and vasoactive intestinal peptide (VIP)/PRL neuroendocrine systems are photoperiodic dependent (18–20) with considerable evidence indicating that central monoamines are involved in their regulation (21–24). Previous studies utilising electrical stimulation, electrolytic lesion or perfusion of neurotransmitters led to the suggestion that a serial neurotransmitter/neuropeptide pathway involving 5‐HT, DA, GnRH‐I and VIP carries photic information, giving rise to the release of LH/FSH and PRL, which are related to photostimulation and ovarian recrudescence (14, 25–28). However, more recently (29), a study in quail has demonstrated that photoinduced TSH synthesis in cells in the pars tuberalis results in increased metabolism of T4 to T3 in basal hypothalamic tanycytes and activation of the reproductive neuroendocrine system.…”
Section: Discussionmentioning
confidence: 99%